Contemporary management and outcomes of blunt thoracic aortic injury. Issue 2 (February 2015) - DuBose, Joseph J.; Leake, Samuel S.; Brenner, Megan; Pasley, Jason; O'Callaghan, Thomas; Luo-Owen, Xian; Trust, Marc D.; Mooney, Jennifer; Zhao, Frank Z.; Azizzadeh, Ali
<x xml:space="preserve">Abstract</x> BACKGROUND Blunt thoracic aortic injuries (BTAIs) are composed of a spectrum of lesions ranging from intimal tear to rupture, yet optimal management and ultimate outcome have not been clearly established. METHODS This is a retrospective multicenter study of BTAIs from January 2008 to December 2013. Demographics, diagnosis, treatment, and in-hospital outcomes were analyzed. RESULTS Nine American College of Surgeons–verified Level I trauma centers contributed data from 453 patients with BTAIs. After exclusion of patients expiring before imaging (58) and transfers (13), 382 patients with imaging diagnosis were available for analysis (Grade 1, 94; Grade 2, 68; Grade 3, 192; Grade 4, 28). Hypotension was present on admission in 56 (14.7%). Computed tomographic angiography was used for diagnosis in 94.5%. Nonoperative management (NOM) was selected in 32%, with two in-hospital failures (Grade 1, Grade 4) requiring endovascular salvage (thoracic endovascular aortic repair [TEVAR]). Open repair (OR) was completed in 61 (16%). TEVAR was conducted in 198 (52%), with 41% of these requiring left subclavian artery coverage. Complications of TEVAR included endograft malposition (6, 3.0%), endoleak (5, 2.5%), paralysis (1, 0.5%), and stroke (2, 1.0%). Six TEVAR failures were treated by repeat TEVAR (2) or OR (4). Overall in-hospital mortality was 18.8%, and aortic-related mortality was 6.5% (NOM, 9.8%; OR, 13.1%; TEVAR, 2.5%) (Grade 1, 0%; Grade 2, 2.9%; Grade 3, 5.2%; Grade 4, 46.4%). The majority of aortic-related deaths (18 of 25) occurred before the opportunity for repair. Independent predictors of aortic-related mortality among BTAI patients were higher chest Abbreviated Injury Scale (AIS) score, grade, and Injury Severity Score (ISS); TEVAR was protective (p = 0.03; odds ratio, 0.21; confidence interval, 0.05–0.88). CONCLUSION Failures and aortic-related mortality of NOM following BTAI Society of Vascular Surgery Grade 1 to 3 injuries are rare. TEVAR seems independently protective against aortic-related mortality. Early complications of TEVAR have decreased relative to previous reports. Prospective long-term follow-up data are required to better refine indications for intervention. LEVEL OF EVIDENCE Level IV.